Identifying and addressing pill aversion in adults without physiological‐related dysphagia: A narrative review. Issue 12 (2nd August 2022) - McCloskey, Alice P.; Penson, Peter E.; Tse, Yincent; Abdelhafiz, Majadah A.; Ahmed, Shah N.; Lim, Emma J.
Abstract : Solid oral dosage forms (SODFs) (often called pills by patients) are the default formulation to treat medical ailments. Beneficial therapeutic outcomes rely on patients taking them as directed. Up to 40% of the population experience difficulties swallowing SODFs, resulting in reduced adherence and impaired therapeutic efficacy. Often associated with children, this also presents in adults with dysphagia, and without any organic dysphagia (non‐physiological‐related or functional dysphagia). This review aims to identify and appraise current interventions used to screen for and overcome pill aversion in adults with functional dysphagia. A comprehensive search of the literature was conducted. Articles reporting pill aversion in adults aged ≥18 years with no underlying cause, history of, or existing dysphagia were included. Study quality was determined using the STROBE tool for observational studies. A narrative synthesis of the findings was prepared. We identified 18 relevant cohort studies, which demonstrate that pill aversion is a global problem. Perceived ease of and/or SODF swallowability appears to be influenced by female gender, younger age, co‐morbidities (e.g., depression), and physical SODF properties. Patients often modify their medicines rather than raise this issue with their healthcare team. Screening for pill aversion is haphazard but controlled postural adjustments, coating SODFs and behavioural interventions appear to be successful solutions. SODF swallowing difficulties are a barrier to effective medication use. Healthcare professionals must recognise that pill aversion is a problem requiring identification through effective screening and resolution by training interventions, appropriate formulation selection or specialist referral.